Syllabus Design of English Club: Fostering Joyful Extracurricular for Tenth Graders - Mashudi, Aziz; Indah, Rohmani Nur; Syaifulloh, Burhanudin (JOLLT Journal of Languages and Language Teaching, 2023)
The transition from online to onsite English classroom resulted in the challenge for tenth graders to be more skillful in actively engaging into English conversation activities. However, it requires better planning of English Club as curricular lesson to enhance student’s participation. This study was intended to develop the syllabus of English Club to be a joyful extracurricular for tenth graders at a senior high school in Daha Kediri. The need analysis used questionnaire and interview to find the required data of student’s speaking practice in English Club activities. The findings show that English Club plays an important role in supporting students to practice speaking. The students also thought that the English Club had a great way of encouraging their motivation to practice speaking with friends. In other words, English Club gives them more joyful experience and knowledge from the learning atmosphere which is fun and comfortable making them more interested in practicing speaking.